(untitled) (Research, Society and Development, 2021)
Parturition has always been a special moment in women’s lives, as it is responsible for the transition from the female role to motherhood. The aim of the study is to discuss obstetric violence addressing the contribution of nursing in the humanization of parturition. This is an integrative literature review with a qualitative approach, carried out through research in electronic journals, books and legislation relevant to the subject. Obstetric violence violates the dignity of the parturient and leaves trauma and psychological problems, so the humanization of childbirth and the multidisciplinary team is an important instrument to break this practice. The data highlighted the need for legislation to define this type of violence as well as criminalize it by stipulating repressive penalties. It was evident that nursing has a very important role in assisting the parturient, as it is the professional who spends more time next to the parturient patient, who had their mother’s fears and anxieties about childbirth. In this sense, listening to the mother and transmitting her security, respecting this moment, is recognizing the woman as the central subject of the parturition, this recognition makes the principle of human dignity effective. With regard to humanization, the involvement of all professionals who assist the parturient in continuing education and frequent training actions is essential.